Salt transport in the lower South Platte River - Gomez-Ferrer, Ramon V., author; Hendricks, David W., author; Environmental Engineering Program, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1982)
This work demonstrates how river salinity may be characterized, in terms of both time and space variations. Fifteen years of daily and monthly salinity and flow data have been reduced to monthly, seasonal, and annual statistical characterizations for five river stations and three tributary stations for the lower South Platte River. From these characterizations distance profiles were plotted for flow, TDS, and salt mass flows. The distance profiles and measurements of diversion flows, tributary flows, and point source discharges were the basis for a reach by reach materials balance analysis for four reaches of the South Platte River between Henderson and Julesburg. Return flows and return salt mass flows were computed as residuals. The analysis showed that there is not a salt balance in the lower South Platte River. A net salt loss to the land of 380 tons per day occurs by irrigation. The analysis provided can be the basis for a more comprehensive materials balance model. But the results can be used to estimate the impact of new water resources developments upon the salinity regime of the lower South Platte River.
CER81-82RVG-DWH35.
Environmental Engineering Technical Report No. 82-3141-01.
Project 15-1372-3141 Water Quality Problems of Colorado, Colorado State University Experiment Station.
Project 53-1372-1690 Dissolved Solids Hazards in the South Platte River Basin, Colorado Water Resources Research Institute.
Keywords: Saline waters -- South Platte River Watershed (Colo. and Neb.); Water quality -- South Platte River Watershed (Colo. and Neb.)